How Inequalities in Academic Performance Evolve in Lower Secondary School in France: A Longitudinal Follow-up of Students - (:unkn) unknown (My University, 2019)
By focusing separately on social inequalities in academic success and in track orientation, the sociology of education in France tends to overlook inequalities in performance over time. Yet these inequalities are forged throughout the school career. Drawing on a representative sample of students entering the first year of lower secondary school in 2007, this article examines the social inequalities in performance in French and mathematics that develop between the first and last years of lower secondary. We show that differences by social class, gender, and parents’ countries of birth widen during the years in lower secondary school, to the disadvantage of working-class students, boys, and children with parents born in the Maghreb and sub-Saharan Africa. We study the role of the school environment and show that the decline in performance of children with parents from the Maghreb or sub-Saharan Africa can be explained by their over-representation in compensatory education schools, their less frequent retention in the private sector, and their concentration in the Paris region. We find that the school environment does little to explain the widening of the gap between social classes and between boys and girls.
Keywords: African Research